Technology of concentrated training as one of ways to optimization students’ basketball trainings - H.Z. Lavrin (Physical Education of Students, 2017)
Urpose: to find out effectiveness of concentrated training technology in students’ basketball trainings. Material: 55 students participated in experiment. The research was being conducted during one academic year. Skillfulness in basketball techniques was determined with the help of tests’ complex. We assessed: basketball techniques’ fulfillment and their quantitative parameters (quickness of dribbling, passes, movements and accuracy of hitting in basket). Every student was offered to fulfill 7 tests, by results of which we assessed their techniques. Every test was assessed by 12-points’ scale. Results: We proved that for students, who did not practiced basketball trainings beforehand, it is possible to master basketball material. For saving time it was envisaged to master minimal quantity of techniques, required and sufficient for playing basketball. It was found that the technology of concentrated basketball training does not influence on students’ somatic health. Conclusions: Criterion of the mentioned technology’s effectiveness was the level of students’ mastering of basketball techniques and their basketball playing in general. It is noted that basketball training increases effectiveness of mastering of other sport disciplines. Systemic practicing of basketball resulted in students’ success in envisaged by curriculum light athletic and gymnastic.